PARTICIPATORY ACTION RESEARCH - Mu'man Nuryana (Sosio Informa, 2005)
Sebuah Kerangka Kerja bagi Action Research dalam Pengembangan Komunitas dan Pendidikan Populer - This paper helps to elaborate about how researchers, teachers and educational advisors balance their different roles in participatory action research teams. Through explaining the Participatory Action Research (PAR) as a way of building bridges and making connections between people, this method of doing research depicted a process that seeks to develop a practical knowledge and understanding of social, political, environmental, or economical conditions. By using PAR on of research and development, we can recognize our social relationships and the value of our real experiences and personal thoughts and feelings. Moreover, PAR seeks to link the research process to the process of social change; it recognizes the change process as a researchable topic; it brings the research process full circle with people's interests in finding practical solutions for common problems and issues of concern by uniting action and reflection, theory and practice; it involves doing research to define a problem as well as applying the information in action towards solutions to identified problems; it is research conducted by, with and for people, rather than research on people; it is participatory in that it is a necessary condition that people play key roles in and have relevant information about the social system, or community, under study, and that they participate in the research design and implementation of action plans based on research outcomes.